MAHAR MITSLI DALAM PROSESI BAATUR JUJURAN PADA TRADISI PERKAWINAN ADAT BANJAR KALIMANTAN SELATAN - Ramadhan, Abdul Rahman; Saputra, Anjas; Nugroho, Kevin Zidane; El Farabi, Muhammad Nadzif; Rizqi, Muhammad Naufal (Proceedings of International Conference on Islamic Civilization and Humanities, 1970)
This research aims to analyze the amount of jujuran given in the Baatur Jujuran procession in the Banjar traditional marriage tradition of South Kalimantan by considering the concept of mahr mitsli in the perspective of Islamic law. One of the distinctive traditions in Banjar traditional marriage is the Baatur Jujuran procession, which is the moment when the male party gives jujuran to the female party as part of the marriage preparation. The jujuran can be in the form of property, money or other valuables, which are handed over as part of the marriage agreement. However, in relation to the principles of Islamic law, the question arises whether the amount of jujuran submitted in the Baatur Jujuran procession is included in the concept of mahr mitsli or not. This research is qualitative research with literature study data collection technique and content analysis as data analysis technique. The data sources used in this research are secondary data such as books, research journals, scientific articles, and official websites that contain information relevant to the research topic. The results of this research show that the nominal amount determined in the baatur jujuran procession is not a mitsli dowry regulated in Islamic law, the amount of jujuran in Banjar society is a gift or fee charged to the groom to be handed over to the bride.